2003
DOI: 10.1097/01.sla.0000055273.58908.19
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Metastasis From 259 Papillary Thyroid Microcarcinomas

Abstract: Patients who have PTMC presenting with palpable lymphadenopathy should have therapeutic node dissection. Prophylactic node dissection is not beneficial in those without palpable lymphadenopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
211
9
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(249 citation statements)
references
References 21 publications
24
211
9
5
Order By: Relevance
“…In contrast, however, the prevalence of clinical thyroid papillary carcinoma was 1.9-11.7 per 100,000 females of all ages [3,10], which is about 1,000 times lower than that of PMC detected on ultrasonography. The marked difference between these prevalences suggests that PMC rarely grow and become clinically apparent, prompting the question of whether immediate surgery is mandatory for all PMC detected on mass screening, although PMC is also known to show multicentricity in 15-44% of lesions and regional lymph node metastasis in 14-64% of lesions [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, however, the prevalence of clinical thyroid papillary carcinoma was 1.9-11.7 per 100,000 females of all ages [3,10], which is about 1,000 times lower than that of PMC detected on ultrasonography. The marked difference between these prevalences suggests that PMC rarely grow and become clinically apparent, prompting the question of whether immediate surgery is mandatory for all PMC detected on mass screening, although PMC is also known to show multicentricity in 15-44% of lesions and regional lymph node metastasis in 14-64% of lesions [11][12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…El elevado porcentaje de multifocalidad y compromiso local o regional justifica realizar una tiroidectomía total y en aquellos casos en que se detecte multifocalidad, compromiso ganglionar, invasión capsular o vascular, asociar terapia ablativa con radioyodo. Esta experiencia es semejante a la comunicada por otros autores, quienes señalan que debido a la alta proporción de pacientes con cáncer papilar multifocal, aun con tumores pequeños sería necesario realizar una tiroidectomía total, ya que existe el riesgo de dejar tejido tumoral en el lóbulo contralateral [4][5][6]11 . También existe una mayor recurrencia tumoral cuando se realiza solo lobectomía 12 , se aumenta el riesgo de crecimiento nodular benigno 13 y se complica el seguimiento mediante el uso de tiroglobulina.…”
Section: Discussionunclassified
“…En la actualidad, se han identificado como factores de riesgo de comportamiento más agresivo de los MCT la multifocalidad 4 , la presencia de linfonodos metastásicos 5,6 , compromiso de la cápsula del linfonodo 6,7 y la presencia de metás-tasis a distancia 4 . La variedad familiar del MCT también tendría un comportamiento más agresivo 8 .…”
unclassified
“…Wada et al who did prophylactic central compartment lymphadenectomy in clinically node negative patients with microPTC who underwent thyroidectomy, reported that up to 60.9% had involved nodes [14]. Larger primary lesions, follicular variant of microPTC and the extension of the lesion beyond the thyroid capsule are identified as risk factors for lymph node metastasis [4].…”
Section: Pathologic Characteristicsmentioning
confidence: 99%